Platinum‐resistant recurrent ovarian cancer with long survival on bevacizumab and gemcitabine. Issue 7 (16th May 2018) - Komiyama, Shinichi; Kugimiya, Tsuyoki; Takeya, Chiaki; Takahashi, Rena; Kubushiro, Kaneyuki
Abstract: Platinum‐resistant recurrent ovarian cancer has a poor prognosis, but combined therapy with bevacizumab and anticancer agents may be useful. We report a patient with long‐term disease control by the combination of bevacizumab and gemcitabine (BEV + GEM). The patient was a 77‐year‐old woman with high‐grade Stage IIIC serous ovarian carcinoma. In 2012, a complete response (CR) was obtained by neoadjuvant and adjuvant chemotherapy using paclitaxel plus carboplatin and tumor debulking surgery. After recurrence in 2013, CR was achieved again with gemcitabine plus carboplatin. In 2014, recurrence was detected again, but CR was achieved by third‐line combination therapy with gemcitabine, carboplatin and bevacizumab. In 2015, the third recurrence was found during bevacizumab maintenance therapy. Fourth‐line treatment was initiated with BEV + GEM, which has maintained stable disease for 29 months. This is the first report about marked prolongation of survival by BEV + GEM in a patient with platinum‐resistant recurrent ovarian cancer.